De novo Food Allergy After Pediatric Liver Transplantation: A Systematic Review - Bergamo, Chiara; Argento, Emily Claire; Giampetruzzi, Stefania; Cutini, Maristella; Ciabattoni, Francesco; Faggian, Giovanna; Gaio, Paola; Bosa, Luca; Cananzi, Mara (Frontiers in Pediatrics, 2022)
Background: Liver transplant (LT) recipients, particularly children, have an increased risk of developing de novo food allergies (FAs) after transplantation both compared to all the other transplant groups and to the general population. Little is known about the pathogenesis underlying this phenomenon and comprehensive recommendations or clinical practice guidelines are still lacking, mainly due to the scarcity of high-quality evidence. Aim We aimed to prepare a systematic review on de novo FA in pediatric LT recipients to assess epidemiology and risk factors, evaluate the correlation to specific food groups, describe clinical manifestations, investigate the rate of tolerance acquisition over time and report available therapeutic strategies. Methods We conducted this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). MEDLINE, Scopus, Web of Science, Wiley online library, Cochrane Library, and ClinicalTrials.gov databases were systematically searched for studies published from January 1980 to September 2021. All the articles were checked independently by two reviewers in two steps. A total of 323 articles were screened, and 40 were included for data extraction. Results and Conclusions We found that de novo FAs develop in the 15% of pediatric LT recipients, especially in the first 2 years after surgery, with higher risk related to younger age at transplantation (especially <2 years of age) and tacrolimus immunosuppression. Subjects are often allergic to multiple foods, and 15% of them suffer from anaphylaxis. The majority of patients do not spontaneously outgrow their symptoms during follow-up. The discontinuation of tacrolimus in favor of cyclosporine or the association of tacrolimus with mycophenolate have been associated with the resolution or the improvement of FA in small retrospective case series and could be considered in case of severe or multiple, difficult to manage FAs. Prospective multicenter studies are needed to confirm these findings, guide the risk-based stratification of pediatric LT recipients, and provide for high-evidence therapeutic strategies for children with de novo FA.